The Effectivity of Bioinoculants on Suppressing Tylenchulus semipenetrans in Citrus Growing Soil in Cao Phong, Hoa Binh - Thu, Tran Thi Tuyet; Thi Thao, Nguye; Quang Phap, Trinh (VNU Journal of Science: Earth and Environmental Sciences, 2019)
Tylenchulus semipenetrans causes serious damages related to decline on citrus in Cao Phong district, Hoa Binh province. This study evaluated the effects of EM, AMF, AT+Ketomium and Chitosan-Super in the control of nematodes. In the laboratory condition, the T.   semipenetrans was isolated from the soil and assessed for survival in the liquid medium containing EM and Chitosan-Super. The larval mortality rate reached 98.57% after 72 hours when using Chitosan-Super at 2% concentration. For pot experiments, T. semipenetrans and bioinoculants were infected into Hoa Binh red grapefruit rhizospheres. The results indicated that nematode density in the soil decreased the most in CT5 (Chitosan-Super), followed by CT4 (AT+Ketomium), CT3 (AMF+EM) and CT1 (AMF), CT2 (EM); nematode density in roots was the highest at CT5 of 132±27 individuals/5g of roots, while in CT1 there was no parasitic nematode on the red grapefruit root though its density in soil was high (2.424±125 individuals/250g of soil). Citrus grew normally in all of the experience formulas. Research results are an important basis for effective use of bioinoculants in preventing nematode parasitic on citrus.